Phytochemical characterization and fungal screening of Sonneratia apetala fruit and products: Pectin and vitamin C extraction, amino acids and antioxidant activity - Md. Ripaj Uddin; Muhammad Abdullah Al Mansur; Hayatullah; Debabrata Karmakar; Nisat Taslum Jhumur; Amena Kibria; Shyama Prosad Moulick; Abubakr M. Idris (PLoS ONE, 2026)
The increasing demand for sustainable bio-resources has spurred interest in underutilized species like Sonneratia apetala , a mangrove with traditionally consumed fruits. This study provides a comprehensive biochemical and microbiological profile of S. apetala fruit and its derived products (jam, jelly, and pickle), integrating nutritional valorization with safety assessment. Pectin was extracted via acid hydrolysis and ethanol precipitation, yielding 2% with high purity (99.9%), confirmed by FT-IR and NMR spectroscopy. Vitamin C was isolated with a 1% yield and 99.9% purity, verified by HPLC and NMR. Amino acid profiling revealed the raw fruit was rich in essential amino acids, notably histidine (26.6 mg/g). Processing significantly degraded most amino acids, though histidine showed remarkable stability (16.4–17.8 mg/g). Antioxidant analysis demonstrated exceptional activity; the ethyl acetate root extract exhibited a potent DPPH IC₅₀ of 0.74 µg/mL, surpassing many synthetic antioxidants, alongside high Total Phenolic and Flavonoid Contents (555.8 mg GAE/100g DW and 240.6 mg QE/100g DW, respectively). A strong correlation was observed between phenolic content and antioxidant capacity. Crucially, fungal screening showed no detectable growth (<10 CFU/mL) in all samples, indicating product safety and stability. In conclusion, S. apetala fruit is a promising source of high-quality pectin, vitamin C, and potent antioxidants, with processed products being microbiologically stable. This research positions S. apetala as a valuable, multi-purpose species for nutraceutical and food industrial applications, with recommendations for further investigation into specific root antioxidants and scaled-up pectin extraction.